2021
DOI: 10.3389/fimmu.2020.623693
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cells Ameliorate Cisplatin-Induced Renal Fibrosis via miR-146a-5p/Tfdp2 Axis in Renal Tubular Epithelial Cells

Abstract: Mesenchymal stem cells (MSCs) have regenerative properties in acute kidney injury (AKI). However, the potential function of MSCs in chronic kidney disease remains elusive. Renal fibrosis is the common endpoint of chronic progressive kidney diseases and causes a considerable health burden worldwide. In this study, the protective effects of bone marrow mesenchymal stem cells (BM-MSCs) were assessed in repeated administration of low-dose cisplatin-induced renal fibrosis mouse model in vivo as well as a TGF-β1-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Our data also showed that TGF-β1 could effectively promote the expression of Col-I, α-SMA, and Col-III and result in LF cell fibrosis in a dose-dependent manner. According to previous literatures [ 11 , [43] , [44] , [45] ], 10 miRNAs relative to fibrosis were selected as candidates; the RT-qPCR validation of these candidates partially matched the results reported in a previous study [ 46 ]. Since the amelioration of LFH after the EV injection was found, we hypothesised that the miRNAs enriched in the EVs would take responsibility for this amelioration.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our data also showed that TGF-β1 could effectively promote the expression of Col-I, α-SMA, and Col-III and result in LF cell fibrosis in a dose-dependent manner. According to previous literatures [ 11 , [43] , [44] , [45] ], 10 miRNAs relative to fibrosis were selected as candidates; the RT-qPCR validation of these candidates partially matched the results reported in a previous study [ 46 ]. Since the amelioration of LFH after the EV injection was found, we hypothesised that the miRNAs enriched in the EVs would take responsibility for this amelioration.…”
Section: Discussionmentioning
confidence: 85%
“…MiR-146a-5p and miR-221-3p have been found to be involved in cell differentiation, proliferation and apoptosis, and they can modulate the inflammatory response and participate in several pathophysiological processes [ [47] , [48] , [49] , [50] , [51] ]. MiR-146a-5p has been demonstrated to reduce hepatic fibrosis [ 52 ], inhibit the expression of fibrosis-related markers in irradiated and TGF-β1-stimulated LX2 cells (human hepatic stellate cell line), reduce skeletal muscle fibrosis after injury, and attenuate cisplatin-induced renal fibrosis [ 44 , 45 , 53 ]. Therefore, miR-221-3p and miR-146a-5p as majorly investigated molecules might be implicated in the progression of LFH, suggesting that upregulation of the expressions of both miRNAs could be a promising strategy for the treatment of LFH.…”
Section: Discussionmentioning
confidence: 99%
“…BMSCs have shown good application prospects for treating clinical diseases [34][35][36]. However, the transplanted BMSCs have high rates of apoptosis in the hypoxic environment of the lesion area, which greatly limits the transplantation efficacy of BMSCs [7].…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism of drug-induced AKI is oxidative stress. Drug nephrotoxicity directly acts on the proximal renal tubules and causes cell damage, such as mitochondrial dysfunction, lysosomal hydrolase inhibition, phospholipid damage, and increased intracellular calcium concentrations, thereby leading to the formation of reactive oxygen species (ROS) (13). The pathogenic mechanisms of ROS have three main aspects: first, nephrotoxic drugs react with cellular antioxidants (such as glutathione) when they are in a highly reactive form (14,15), thus, depleting or inactivating them, leading to the accumulation of endogenous ROS in cells.…”
Section: Drug-induced Aki and Common Nephrotoxic Drugs: The Cisplatin Examplementioning
confidence: 99%